Effects of serum amyloid protein A on influenza A virus replication and viral interactions with neutrophils. Issue 1 (17th November 2020) - White, Mitchell R.; Hsieh, I‐Ni; De Luna, Xavier; Hartshorn, Kevan L.
Abstract: Innate immunity is vital for the early control of influenza A virus (IAV) infection. Serum amyloid A (SAA1) is an acute phase reactant produced in the liver and lung that rises dramatically during IAV infection. The potential role of SAA1 in host defense against IAV is unknown. SAA1 has been reported to directly activate neutrophils and to recruit them to the lung during infectious and inflammatory processes. Neutrophils are the most abundant cell recruited to the lung in the early phase of IAV infection. There are different forms and preparations of SAA1 that have found to have different effects on phagocyte responses, through various receptors. In this paper, we test the direct effects of various preparations of serum derived or recombinant SAA on IAV and how it modulates the interactions of IAV with neutrophils. All SAA preparations bound to IAV in vitro but caused minimal hemagglutination inhibition or viral aggregation. The human serum‐derived SAA1 or the complex of SAA1 with HDL did have IAV neutralizing activity in vitro, whereas the recombinant SAA1 preparations did not. We found that different SAA preparations also had markedly different effects on neutrophil functions, with E. coli ‐derived SAA1 triggering some responses in neutrophils on its own or in presence of IAV whereas mammalian cell‐derived SAA1 did not. This discrepancy could be explained by the reported contamination of the former preparation with bacterial components. Of interest, however, serum SAA alone, serum SAA complexed with HDL, or HDL alone potentiated some neutrophil responses to IAV. Our results suggest that SAA may play some role in host response to IAV, but further work needs to be done to clarify the role of different variants of SAA alone or complexed with HDL. Graphical Abstract: Serum amyloid a protein (SAA) bound to and inhibited influenza virus infectivity, but SAA free of bacterial products did not alter neutrophil responses.